The effect of budgetary participation on managerial performance: internal control and organizational commitments as intervening variables - Hendrik Sastrawan; Fajar Gustiawaty Dewi; Yuliansyah Yuliansyah (Goodwood Publishing, 2020)
Purpose: This study aims to examine the effect of budgetary participation on managerial performance with internal control and organizational commitment as an intervening variable, in a state-owned plantation company, namely PT Perkebunan Nusantara VII. Research methodology: Using a questionnaire survey study for 100 respondents involved in the budgeting process at PT Perkebunan Nusantara VII, this study analyzed the data using SEM PLS, SmartPLS 3.2 software. Results: The results show that budgetary participation has a positive effect on managerial performance directly. Meanwhile, internal control is an intervening variable into the relationship between budgeting participation and managerial performance. On the contrary, organizational commitment is not proven as an intervening variable into the relationship between budgeting participation and managerial performance. Limitations: This study contributes to the management accounting literature and provides an overview of the effectiveness of regulations, policies and work programs that have been made by companies in improving managerial performance, particularly those relating to budgeting, internal control, and organizational commitment. Contribution: The study attempts to offer new insights on the influence of budgeting participation, internal control and organizational commitment, and other variables in improving managerial performance in state-owned plantation companies. Keywords: Budgeting participation, Managerial performance, Internal control, Organizational commitment